E-Screening for Prenatal Depression in Kampala, Uganda Using the Edinburgh Postnatal Depression Scale: Survey Results - Hasifah Kasujja Namatovu; Mark Abraham Magumba; Dickens Akena (Online Journal of Public Health Informatics, 2025)
Abstract BackgroundPerinatal depression remains a substantial public health challenge, often overlooked or incorrectly diagnosed in numerous low-income nations. ObjectiveThe goal of this study was to establish statistical baselines for the prevalence of perinatal depression in Kampala and understand its relationship with key demographic variables. MethodsWe employed an Android-based implementation of the Edinburgh Postnatal Depression Scale (EPDS) to survey 12,913 women recruited from 7 government health facilities located in Kampala, Uganda. We used the standard EPDS cutoff, which classifies women with total scores above 13 as possibly depressed and those below 13 as not depressed. The χ2 ResultsWe found that 21.5% (2783/12,913, 95% CI 20.8%‐22.3%) were possibly depressed. Respondents’ relationship category was found to be the most influential variable (χ21rPrP(rP ConclusionsThis study shows that demographic factors such as spousal employment category, age, and relationship status have an influence on the respondents’ EPDS scores. These variables may serve as proxies for latent factors such as financial stability and emotional support.